THE EFFECT OF PROFITABILITY, LEVERAGE, AND FIRM SIZE ON CASH HOLDING INDUSTRY COMPANY - Hidayati, Nabila Dinar; Ratnawati, Dyah (Yayasan Education and Social Center, 2024)
This study aims to empirically prove the effect of profitability, leverage, and firm size on cash holding in industrial sector companies listed on the Indonesia Stock Exchange during 2019-2022. This research uses quantitative methods. The population in this study amounted to 63 industrial sector companies. The sample used in this study was selected using purposive sampling with predetermined sample criteria. Therefore, the total sample of this study was 22 industrial sector companies. The data used is secondary data obtained from the annual financial statements of selected industrial sector companies. The data is analyzed using multiple linear regression. The results of this study indicate that profitability and leverage influence cash holding, while firm size does not. Suggestions that can be proposed are that future research can add variables that have a stronger relationship. In addition, it is hoped that future research can add a more extended sample or research period that might show better and more accurate results